Subtyping of Cushing’s Syndrome: A Step Ahead - Tizianel, Irene; Barbot, Mattia; Ceccato, Filippo (Experimental and Clinical Endocrinology & Diabetes, 2024)
Cushing’s Syndrome (CS) is a rare disease due to chronic endogenous cortisol secretion. In recent years, new developments have broadened the spectrum of differential diagnosis, traditionally categorized as adrenocorticotropic hormone (ACTH)-dependent and ACTH-independent forms. Moreover, increased awareness of the detrimental effects of cortisol on cardiometabolic health and the risk of cardiovascular events lead to increased diagnosis of mild forms, especially in the context of adrenal incidentalomas.This review provides an up-to-date narrative of the most recent literature regarding the challenges of CS diagnosis. After the description of the diagnostic tools available, the functional non-neoplastic hypercortisolism (formerly known as pseudo-Cushing state) is characterized, followed by the subtyping of the different conditions of hypercortisolism, including the differential diagnosis of ACTH-dependent forms and the management of adrenal hypercortisolism, with peculiar attention to the new genetic classification of adrenal CS, mild autonomous cortisol secretion, and bilateral adrenal adenomas.
Keywords: Cushing’s Syndrome; Cushing’s disease; ectopic ACTH secretion; diagnosis; non-neoplastic hypercortisolism